The Personal brand of a Video Reporter in the Age of Social Media: Challenges and Opportunities - Kovalenko, Yuliia; Prasol, A. (ХДАК, 2024)
A video reporter’s personal brand is generally understood as a unique image and professional reputation, composed of professional skills, personal traits, work style, and interaction with the audience, which collectively make the video reporter recognizable and a trusted source of information. Тoday reporters are not limited in their professional activities to traditional television and radio. With the development of digital media, their work has expanded to include online publications, YouTube and social networks. Among the new formats for traditional video journalism, short videos, live streams, 360-degree videos, and interactive have become popular formats. With new technologies, the role of the reporter - author evolves, as they are now responsible not only for gathering information but also for processing, editing, and directly broadcasting it to the audience. The audience can leave comments, ask questions, and suggest topics for coverage. This interactivity brings reporters closer to their audience and creates a sense of direct involvement. In the digital era, video reporters have become not only carriers of information but also active content creators who use cutting-edge technologies to deliver news in real time.
Keywords: відеожурналістика; художній репортаж